2019
DOI: 10.2478/hukin-2018-0076
|View full text |Cite
|
Sign up to set email alerts
|

Mouth Rinsing Cabohydrates Serially does not Improve Repeated Sprint Time

Abstract: Sensing carbohydrates via the oral cavity benefits performance outcomes during brief high intensity bouts of exercise. However, the extent to which carbohydrates need to be present in the oral cavity to influence sprint performance is less understood. The purpose of this study was to determine if serial increases in carbohydrate rinse time across sprint sets attenuates increases in sprint time compared to no serial increases in carbohydrate rinse time across sprint sets. Fifteen sprint trained participants com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In addition, 10 s of CMR was superior to 5 s during 30 min of self-paced cycling performance [31]. In contrast, high-intensity sprinting [32] and a Yo-Yo intermittent recovery test [33] performance did not increase with serial rinsing of CHO (30 and 80 s, respectively). Previously, three studies [20,25,26] from our laboratory observed no improvement in 40% of bench press 1 RM repetition to failure performance with serial CHO rinsing (20 or 30 s).…”
Section: Discussionmentioning
confidence: 84%
“…In addition, 10 s of CMR was superior to 5 s during 30 min of self-paced cycling performance [31]. In contrast, high-intensity sprinting [32] and a Yo-Yo intermittent recovery test [33] performance did not increase with serial rinsing of CHO (30 and 80 s, respectively). Previously, three studies [20,25,26] from our laboratory observed no improvement in 40% of bench press 1 RM repetition to failure performance with serial CHO rinsing (20 or 30 s).…”
Section: Discussionmentioning
confidence: 84%
“…Sinclair et al (18) reported that cycling performance was improved by doubling the duration (from 5 to 10 s) of the carbohydrate mouth rinse protocol, although their results were recently contradicted by Tomko (36) who found no dose-response effect when increasing the rinse duration from 5 to 15 s. Although more evidence is needed to ascertain the optimal rinsing time, it has been suggested that increasing rinsing duration may interfere with participants’ breathing patterns during high intensity exercise (34), as we found in our familiarization trial. Based on the information available so far, carbohydrate mouth rinsing for 5 s, each 5–10 min of exercise, allows for a significant contact between oral cavity and a carbohydrate source.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of an exercise protocol that elicited peripheral rather than central fatigue may also have surrendered an additional difficulty to reveal the true CHO mouth rinse effects. 78 Indeed, a recent study by Nehme et al 81 found no benefits in performance measured in the Yo-Yo Intermittent Recovery Test Level 1 with serial CHO mouth rinses. Interestingly, neither serial nor single CHO mouth rinses exhibited superior beneficial effects than placebo mouth rinses.…”
Section: Mouth Rinse Durationmentioning
confidence: 95%
“…Perhaps, the CHO mouth rinse duration has been one of the first methodological aspects highlighted as a confounding factor in the literature. However, only a few studies 26 , 46 , 78 , 79 have attempted to verify the influence of longer mouth rinses with CHO solution on exercise performance.…”
Section: Mouth Rinse Durationmentioning
confidence: 99%
See 1 more Smart Citation